The range of diagnoses for oral soft-tissue biopsies of geriatric patients in a Saudi Arabian teaching hospital - Ahmed Qannam; Ibrahim O. Bello (Elsevier, 2016)
Introduction: The increased life expectancy being observed worldwide necessitates careful planning for future geriatric oral health care needs, which should be based on epidemiologic surveys to identify these needs. We aimed to survey the range of lesions diagnosed in soft-tissue biopsies of patients over age 60 over a 30-year period in a Saudi Arabian teaching hospital. Methods: The histopathology records of geriatric patients with complete demographic data who were diagnosed between 1984 and 2013 at the College of Dentistry, King Saud University, were reviewed. The lesions were then classified into eight broad categories. Associations between variables were evaluated using Pearson's Chi square test. Results: There were 231 soft-tissue biopsies obtained from geriatric patients whose complete records were available. The male to female ratio was 1.1:1, and the mean age was 66.7 years. Most lesions (69%) occurred in patents aged 60-69 years. Although reactive lesions were generally the most common, the most common lesions were squamous cell carcinoma and fibroma. Lesions were most commonly located on the buccal mucosa and the alveolar ridge/gingivae. Conclusions: The range of lesions seen in Saudi geriatric patients were similar to those reported for other parts of the world, although the lesions were more similar to those reported from developing countries. The very high rate of oral cancer, however, is expected to take the majority of the resources allocated to geriatric oral health care, except if a strong, population-based prevention program is initiated immediately. Keywords: Geriatric, Oral soft tissue, Biopsies, Saudi Arabia